Case Report: Extensive Tumor Profiling in Primary Neuroendocrine Breast Cancer Cases as a Role Model for Personalized Treatment in Rare and Aggressive Cancer Types - Schaffrin-Nabe, Dörthe; Schuster, Stefan; Tannapfel, Andrea; Voigtmann, Rudolf (Frontiers in Medicine, 2022)
Neuroendocrine Breast Cancer (NEBC) is a rare entity accounting for <0.1% of all breast carcinomas and <1% of all neuroendocrine carcinomas. Treatment strategies in NEBC are largely empirical in absence of prospective clinical trial data on NEBC cohorts. Hierein we present two case reports diagnosed with anaplastic and small cell NEBC. After initial therapies failed comprehensive tumour profiling was applied and led to indivualized treatment options for both patients. In both patients, targetable alterations of the PI3K/AKT/mTOR pathway were found among others, a PIK3CA mutation itself and a STK11 mutation which negatively regulates the mTOR complex. The epicrisis of the two patients exemplifies how to manage rare and difficult to treat cancers and how new diagnostic tools contribute to the medical management.